Հովհաննես Նալբանդյան. հայ առաջին խոշոր ջութակահարը - Ասատրյան, Աննա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Выдающийся скрипач и педагог, Заслуженный артист РСФСР (1926), Заслуженный деятель искусств РСФСР (1937) Иоаннес Романович Налбандян (Ованес Аракелович, 1871–1942) – ярчайший символ армяно-русских музыкальных связей. Родившись в Симферополе (Крым), он долгие годы жил и творил в Петербурге. Северная столица России стала для него второй родиной. Выпускник Петербургской консерватории, профессор И. Р. Налбандян 47 лет преподавал в Петербургской, а затем – в Ленинградской консерватории. Через Налбандяна осуществилась связь ауэровской скрипичной школы с советским скрипичным искусством. Осенью 1890 г. он впервые выступил на армянском студенческом вечере. Именно тогда товарищи-студенты убедили его переменить окончание фамилии «ов» на «ян», чтобы все знали, что он армянин. Директор Петербургской консерватории А. Рубинштейн одобрил это намерение и велел переделать все бумаги․ Outstanding violinist and pedagogue, Honored Artist of the RSFSR (1926), Honored Art Worker of the RSFSR (1937) Hovhannes Romanovich Nalbandyan (Hovhannes Arakelovich, 1871–1942) is the brightest symbol of Armenian-Russian musical ties. Born in Simferopol (Crimea), he lived and acted in St. Petersburg for many years. The northern capital of Russia became his second homeland. A graduate of the St. Petersburg Conservatory, Professor H. R. Nalbandyan taught for 47 years at the St. Petersburg Conservatory, and then at the Leningrad Conservatory. Through Nalbandyan, the connection between the Auer violin school and the Soviet violin art was realized. In the fall of 1890, he made his first appearance at an Armenian student evening. It was then that fellow students convinced him to change the ending of his surname “ov” to “yan” so that everyone would know that he was an Armenian. Director of the St. Petersburg Conservatory A. Rubinstein approved this intention and ordered all the papers to be redone.
Keywords: Երաժշտություն